Building urban and infrastructure resilience through connectivity: An institutional perspective on disaster risk management in Christchurch, New Zealand. (March 2020) - Huck, Andreas; Monstadt, Jochen; Driessen, Peter
Abstract: The management of large-scale disasters in urban agglomerations often reveals fragmented governance structures. Accordingly, recent debates in the field of disaster risk management call for better coordination of agencies and actors across organisational and territorial boundaries, arguing that this would ultimately improve the resilience of urban areas. However, our analysis of the metropolitan area of Greater Christchurch, which experienced a series of devastating earthquakes in 2010/2011, shows that this conclusion inadequately acknowledges the uncertainties and institutional complexities in the governance of resilience. We show that debates on urban resilience can benefit from the concept of institutional connectivity – defined as institutionalised forms of vertical, horizontal or cross-territorial interaction – to systematically address these complexities. Our empirical results suggest that the efficacy of different forms of institutional connectivity depends on prevailing circumstances. Therefore, particular forms of connectivity should be prioritised on a case-by-case basis. Our empirical study reveals that enhancing institutional connectivity is a resource-intensive and contested process that might induce negative trade-offs. We contend that because institutions shape how different agencies and organisations interact, scholarly debates on urban resilience should put more emphasis on processes of institutional reform and stress the political dimension of institution building for urban resilience. Highlights: Implementing urban resilience requires institutional connectivity between actors. Specific forms of connectivity have different impacts on urban resilience. Building resilience is a contested and highly political process. Enhancing connectivity is resource-intensive and might induce trade-offs. The point in time at which connectivity is enhanced matters considerably.